Penundaan Pemilihan Keuchik Langsung Dalam Surat Edaran Sekretaris Daerah Aceh No 400. 10/4007 Tahun 2025 Dalam Perspektif Siyasah Dusturiyah : Postponement of Direct Keuchik Elections in the Circular Letter of the Aceh Regional Secretary No. 400.10/4007 of 2025 From the Perspective of Siyasah Dusturiyah - Nauval Nauval; Sitti Mawar; T. Surya Reza (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This research addresses the legal standing of the Aceh Regional Secretary Circular Letter Number 400.10/4007 of 2025 as the basis for postponing the Direct Village Head Election (Pilchiksung) and its implications for the legitimacy of governmental authority and the protection of the political rights of gampong communities, while also examining its conformity with the principles of justice, trustworthiness, and public welfare within Islamic constitutional law. This normative legal study employs statutory, conceptual, and comparative approaches through an analysis of laws and regulations, state administrative law doctrines, and fiqh siyāsah literature to analyze, first, the legal implications of postponing Pilchiksung in Aceh through the aforementioned circular letter and, second, to assess the policy from the perspective of siyāsah dustūriyyah. The findings show that a circular letter is not part of the hierarchy of legislation with general binding force; therefore, postponing Pilchiksung based on such an instrument constitutes a defect of authority (bevoegdheidsgebrek), contradicts the principles of legality and legal certainty, and potentially violates the democratic political rights of gampong communities. From the perspective of siyāsah dustūriyyah, the postponement policy is inconsistent with the principles of al-‘adālah (justice), al-amānah (trustworthiness), and al-maṣlaḥah al-‘āmmah (public interest), as it delays the people’s rights without a valid legal basis and clear considerations of public welfare. Consequently, this study concludes that postponing Pilchiksung through a circular letter lacks both legal and moral legitimacy and therefore must be corrected through the establishment of a lawful, just, and democratically aligned legal instrument consistent with the values of Islamic constitutionalism.